The effects of amiodarone on thyroid function in pediatric and adolescent patients. Issue 4 (August 2021) - Barrett, Brett; Bauer, Andrew J.
Abstract : Purpose of review: Amiodarone-induced thyroid dysfunction is well established. The present review discusses recent literature related to the effects of amiodarone on the thyroid gland and thyroid function in pediatrics. Recent findings: Current guidelines in adults treated with amiodarone recommend baseline thyroid function testing followed by initiation of thyroid hormone monitoring after 3 months on therapy. Two retrospective studies to evaluate amiodarone-induced thyroid dysfunction in children and young adults reveal thyroid dysfunction as soon as 2 weeks after amiodarone initiation with a greater percentage of pediatric patients developing amiodarone-induced hypothyroidism rather than thyrotoxicosis. Although additional studies are needed to determine if AIH is associated with negative impact on growth and neurocognitive development, what is clear is that in both adults and pediatrics, there is low compliance with recommended side effect-monitoring guidelines. Summary: Pediatric patients are at similarly high risk to develop amiodarone-induced thyroid dysfunction as are adults. It is hoped that through improved education of providers and patients further research into the incidence, the potential risks of amiodarone therapy and the potential benefits of thyroid hormone replacement therapy in patients with AIH will be investigated and reported.